PETROLEUM SYSTEM CEKUNGAN KUTAI BAGIAN BAWAH, DAERAH BALIKPAPAN DAN SEKITARNYA, PROPINSI KALIMANTAN TIMUR - -, Yuyun Yuniardi (Bulletin of Scientific Contribution, 2012)
Oil and gas potential in Lower Kutai Basin were probably exist, those condition have checked from well petroleum system to support oil and gas accumulation in this area. Data integration of source rock, reservoir rock, cap rock, trap assotiation, and migration system in Lower Kutai Basin could be doing advance research to proving oil and gas accumulation.